Simultaneous eruptions from multiple vents at Campi Flegrei (Italy) highlight new eruption processes at calderas - Pistolesi, M; Isaia, R; Marianelli, P; Bertagnini, A; Fourmentraux, C; Albert, P; Tomlinson, E; Menzies, M; Rosi, M; Sbrana, A (Geological Society of America, 2016)
Volcanic eruptions are typically characterized by the rise and discharge of magma at the surface through a single conduit/vent system. However, in some cases, the rise of magma can be triggered by the activation of eruptive fissures and/or vents located several kilometers apart. Simultaneous eruptions from multiple vents at calderas, not related to caldera collapse (e.g., ring faults) are traditionally regarded as an unusual phenomenon, the only historically reported examples occurring at Rabaul caldera, Papua New Guinea. Multiple venting within a caldera system is inherently difficult to demonstrate, owing partly to the infrequency of such eruptions and to the difficulty of documenting them in time and space. We present the first geological evidence that at 4.3 kyr ago the Solfatara and Averno vents, 5.4 km apart, erupted simultaneously in what is now the densely populated Campi Flegrei caldera (Southern Italy). Using tephrostratigraphy and geochemical fingerprinting of tephras, we demonstrate that the eruptions began almost at the same time and alternated with phases of variable intensity and magnitude. The results of this study demonstrate that multi-vent activity at calderas could be more frequent than previously thought and volcanic hazards could be greater than previously evaluated. More generally we infer that the simultaneous rise of magma and gas along different pathways (multiple decrepitation of chamber/s) could result in a sudden pressure rise within sub-caldera magmatic system.